Analisis Pengaruh Massa Sampel, Volume Pelarut, dan Waktu Sonikasi pada Ekstraksi Bawang Merah (Allium ascalonicum L.) terhadap Kandungan Quercetin - Chalif, Charisma; Alauhdin , Mohammad (Universitas Negeri Semarang, 2024)
Shallots (Allium ascalonicum L.) are plants that grow in tropical areas and are commonly consumed by Indonesian people. This plant can be used as medicine because it contains quercetin which has antioxidant activity. The aim of this research was to determine the effect of sample mass to solvent volume ratio as well as sonication time on the extract yield and quercetin content in shallot extraction. This research used an ultrasonic wave-assisted extraction method with ethanol as solvent. The extraction process was carried out at varying ratios of sample mass (g) to solvent volume (mL) of 1:5, 1:10, 1:15 and 1:20 and extraction times of 15, 25 and 35 minutes. The shallot extract obtained was determined its yield and the quercetin content. Quercetin compound level was determined by HPLC. The highest yield was obtained at a ratio of 1:20 with a sonication time of 25 minutes of 73.23% and the highest content of quercetin compound was obtained at a ratio of 1:5 with a sonication time of 35 minutes of 0.342 mg QE/g. The results of the ANOVA analysis showed that the sample mass ratio to solvent volume parameter had a significant effect on the extract yield, while the sonication time factor had no significant effect on the extract yield. Meanwhile, the ratio of sample mass to volume or sonication time did not have an effect on the levels of quercetin compounds obtained